Controlled growth of titanium dioxide nanotubes for doxorubicin loading and studies of in vitro antitumor activity - Zhang, Yunshan; Huang, Tuo; Lv, Wanwan; Yang, Kai; Ouyang, Cuiling; Deng, Minxin; Yi, Rongyuan; Chu, Hui; Chen, Jian (Frontiers in Bioengineering and Biotechnology, 2023)
Titanium dioxide (TiO2) materials are suitable as drug carriers due to their natural biocompatibility and nontoxicity. In this paper, the aim of the present study was to investigate the controlled growth of TiO2 nanotubes (TiO2 NTs) with different sizes via an anodization method, in order to delineate whether NTs size governs drug loading and release profile as well as anti-tumor efficiency. The sizes of TiO2 NTs from 25 nm to 200 nm were tailored in accordance with the anodization voltages. The obtained TiO2 NTs were characterized using scanning electron microscope (SEM), transmission electron microscope (TEM), and dynamic light scattering (DLS). The larger size TiO2 NTs resulted in highly improved doxorubicin (DOX) loading capacity (up to 37.5 wt %) and contributed to the outstanding cell killing ability with a lower half maximal inhibitory concentration (IC 50). Cellular uptake and intracellular release of DOX were carried out using large size TiO2 NTs loaded DOX compared to the small size TiO2 NTs loaded DOX. The results showed that the larger size TiO2 NTs were a promising therapeutic carrier for drug loading and controlled release, which could improve cancer treatment outcomes. Therefore, TiO2 NTs with larger size are useful substances with drug-loading potency that may be used for a wide range of medical applications.